2022
DOI: 10.3390/md20030188
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Vindoline and Catharanthine Accumulation, Antioxidant Enzymes Activities, and Gene Expression Levels in Catharanthus roseus Leaves by Chitooligosaccharides Elicitation

Abstract: Catharanthus roseus (L.) G. Don is a plant belonging to the genus Catharanthus of the Apocynaceae family. It contains more than one hundred alkaloids, of which some exhibit significant pharmacological activities. Chitooligosaccharides are the only basic aminooligosaccharides with positively charged cations in nature, which can regulate plant growth and antioxidant properties. In this study, the leaves of Catharanthus roseus were sprayed with chitooligosaccharides of different molecular weights (1 kDa, 2 kDa, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Chitin is a major cell wall constituent of fungus (Liaqat and Eltem, 2018) Chitooligosaccharides derived from chitin are elicitors of innate immune defense against fungal pathogens. Treatment of C. roseus leaves using 0.1 mg/ml of a 3 kDa molecular weight commercially available chitooligosaccharide extraction led to an increase of the vinblastine precursors vindoline and catharanthine of 60.68 and 141.54% (Tang et al, 2022). In C. roseus cambial meristematic cell cultures adding 25 mg/l mycelium elicitor from the fungus Aspergillus flavus resulted in fold increases of 1.45 for vindoline, 3.29 for catharanthine, and 2.14 for ajmaline (Liang et al, 2018).…”
Section: Pathogen Defense Elicitationmentioning
confidence: 99%
“…Chitin is a major cell wall constituent of fungus (Liaqat and Eltem, 2018) Chitooligosaccharides derived from chitin are elicitors of innate immune defense against fungal pathogens. Treatment of C. roseus leaves using 0.1 mg/ml of a 3 kDa molecular weight commercially available chitooligosaccharide extraction led to an increase of the vinblastine precursors vindoline and catharanthine of 60.68 and 141.54% (Tang et al, 2022). In C. roseus cambial meristematic cell cultures adding 25 mg/l mycelium elicitor from the fungus Aspergillus flavus resulted in fold increases of 1.45 for vindoline, 3.29 for catharanthine, and 2.14 for ajmaline (Liang et al, 2018).…”
Section: Pathogen Defense Elicitationmentioning
confidence: 99%
“…Moreover, several studies showed that the use of COS is a promising option to increase the production of secondary metabolites with pharmacological significance. Thus, COS improved the pharmaceutical value of Catharanthus roseus (L.) G. Don by increasing the content of vindoline and catharanthine in the leaves, and by increasing the fresh weight of roots, stems and leaves (Tang et al, 2022). Moreover, greek oregano (Origanum vulgare ssp.…”
Section: Introductionmentioning
confidence: 99%
“…catalyzes the synthesis of strictosamide (STR) from geraniol diphosphate and tryptamine in cytoplasm [8,9]. Previous research has shown that chitooligosaccharides, the only positively charged basic amino oligosaccharides in nature, can induce the expression of STR and other genes, thereby improving the drought tolerance and yield of plants [10][11][12].…”
Section: Introductionmentioning
confidence: 99%